Development of Food Plot at The South China Sea of Indonesia's Outer Island - Lukman Hakim, Dani (International Journal of Regional Innovation, 2025)
Establishing food plot in the outer island of Indonesia constitutes a strategic approach to bolstering food security and promoting agricultural sustainability. This study investigates the establishment and consequences of food plot on diverse remote islands in Indonesia. The key objectives encompass assessing soil suitability, determining appropriate crop selection, and implementing agricultural practices tailored to specific local climatic and environmental conditions. The study utilizes a mixed-methods methodology, incorporating soil analysis, crop yield evaluations, and interviews with local farmers and agricultural specialists. There are 14 SMUs in Anambas Islands Regency, that are created by layering various thematic maps such as those showing soil composition, topographic features, land use patterns, and climate data, including precipitation levels. Based on the results of the analysis of field and laboratory data, the actual land suitability class for lowland rice commodities was obtained based on the existing potential in the Anambas Islands Regency Area. From the existing soil map units (SMU), all SMU representative points are declared "marginally suitable" for lowland rice commodities, with suitability class S3. Meanwhile, in the subclasses, the inhibiting factors found were quite diverse, such as limited nutrition (nr) and oxygen availability (oa). Community empowerment in Anambas Islands Regency serves as a fundamental determinant in fostering sustainable development and improving the overall well-being of individuals residing within a community. The objective is to enhance the capacity of community members to exercise autonomy in their lives, facilitate informed decision-making, and collaboratively address challenges.